Assessment of the influence of landfill leachate on the growth of energy willow - Nowak, Rafał (Instal, 2022)
The large-scale cultivation of the energy willow (Salix viminalis) can contribute the fuel crisis caused by the current geopolitical situation and reduce the need to import solid fuels to Poland. Apart from purely political aspects, such a solution is supported by low investment costs, simplicity of cultivation, and a rapid increase in willow biomass. Using landfill leachate to intensify cultivation instead of artificial fertilizers can be particularly useful. The leachate, wastewater generated in municipal landfills, is characterized by high concentrations of nitrogen compounds and micronutrients necessary for developing green plants. Therefore their use is considered advisable.
Keywords: energy willow; renewable energy sources; leachate